2012
DOI: 10.1007/s11920-012-0271-1
|View full text |Cite
|
Sign up to set email alerts
|

Deinstitutionalization? Where Have All the People Gone?

Abstract: Although there is broad consensus that the state psychiatric hospital population drastically declined over the past five decades, the destination and well-being of people with serious mental illness (SMI) have been in greater doubt. In this article, we examine the aftermath of the deinstitutionalization movement. We begin with a brief historical overview of the move away from state hospitals, followed by an examination of where people with SMI currently reside and receive treatment. Next, we review recent tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 66 publications
1
23
0
Order By: Relevance
“…Davis, Fulginiti, Kriegel and Brekke (2012) indicated that the current U.S. decentralized community-based model of mental health care has generally benefited middle-class individuals with less severe disorders, while those with serious and persistent mental illness, with the greatest need, often fare the worst -a statement backed up by Pollack (2013). Underfunding by local and federal governments is reported by many authors (Davis et al, 2012;Pollack, 2013;Yohanna, 2013) as a probable cause of this limited success.…”
Section: Discussionmentioning
confidence: 99%
“…Davis, Fulginiti, Kriegel and Brekke (2012) indicated that the current U.S. decentralized community-based model of mental health care has generally benefited middle-class individuals with less severe disorders, while those with serious and persistent mental illness, with the greatest need, often fare the worst -a statement backed up by Pollack (2013). Underfunding by local and federal governments is reported by many authors (Davis et al, 2012;Pollack, 2013;Yohanna, 2013) as a probable cause of this limited success.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively younger schizophrenics, who were discharged into the "community," received only treatment, but no care (Scull, 1984;Bachrach, 1976;Bassuk & Gerson, 1978). This model worked for some, if their problems were not too severe; if their illness was episodic; and if they had medical insurance, since Federal funding for the CMHCs dried up over time (Davis et al, 2012). For the large group of poor, chronic, severely disabled, however, this model proved a vicious circle.…”
Section: Carementioning
confidence: 99%
“…First, no known studies provide descriptive information on the patterns of suicidal disclosure among individuals with SMI engaged in community‐based psychiatric treatment. Not only are individuals with SMI at increased risk for suicidal outcomes, they are increasingly receiving care in less restrictive settings (Davis, Fulginiti, Kriegel, & Brekke, ), where disclosure may be even more critical to suicide risk management. Second, several individual‐level factors found to be central to disclosure of other stigmatized statuses, such as social support and perceived stigma, have not been explored in relation to suicidal disclosure.…”
mentioning
confidence: 99%